Assessment of the Distribution, Sources and Potential Ecological Risk of Heavy Metals in the Dry Surface Sediment of Aibi Lake in Northwest China - Abuduwaili, Jilili (PLoS One, 2015)
The distribution, sources and potential ecological risk of heavy metals in the sediment of lakes in eastern China and other areas of the world that have undergone rapid economic development have been widely researched by scholars. However, this is not true for heavy metals in the sediment of rump lakes in the arid regions of China and world-wide. Because of this, we chose Aibi Lake to serve as a typical rump lake in an oasis in an arid area in northwest China for our study. Sediment samples were collected from the lake and then the quantities of the heavy metals Pb, Ni, Cd, Cu, Zn, Hg and Cr were measured. Then using a variety of statistical methods, we analyzed the distribution, sources, pollution status and the potential ecological risk of these metals. The results show that: (1) The amounts of the seven heavy metals all fell within the Second Soil National Standard, but the average and maximum values were all higher than the background values of Xinjiang in northwest China. (2) Multivariate statistical analysis determined that the Cd, Pb, Hg and Zn in the sediment were mainly derived from man-sources, and Cu, Ni, and Cr were mainly from the natural geological background. (3) Enrichment factor analysis and the geo-accumulation index evaluation method show that Cd, Hg and Pb in the surface sediment of the Aibi Lake were at low and partial pollution levels, while Zn, Cr, Ni and Cu were at no and low pollution levels. (4) Calculation of the potential ecological hazards index found that, among the seven tested heavy metals, Cd, Hg and Pb were the main potential ecological risk factors, and the contribution of each was 42.6%, 28.6%, and 24.0%, respectively. Cd is the main potential ecological risk factor, followed by Hg and Pb. This work revealed that recent economic development of the Aibi Lake Basin has negatively influenced the accumulation of heavy metals in the sediments of the lake, and, therefore, we should pay increasing attention to this problem and take effective measures to protect the ecology of the Aibi Lake Basin. This work can provide a scientific basis for an early warning of heavy metal pollution and for protection of the environment. Furthermore, it can serve as a reference when creating policies for the economic development in Aibi Lake Basin and environmental protection of rump lakes in arid regions of northwest China and other areas of the world.